Spin Retry Count Relation with Other Hdd Parameters - Nailovich Nasyrov, Iskandar; Iskandarovich Nasyrov, Ildar; Iskandarovich Nasyrov, Rustam; Askarovich Khairullin, Bulat (International Journal of Psychosocial Rehabilitation, 2019)
The change of the SMART parameter 10 Spin retry count values depending on the operating time is considered; this parameter characterizes the number of repeated attempts to spin the disks up to operating speed if the first attempt was unsuccessful. This parameter is critical in the sense that if the value of the attribute increases, then the likelihood of malfunctions in the mechanical part of the hard disk drives is high. The scientific task of the study is to establish the relationship between this parameter in failed hard drives and the values of other reliability parameters for information stores from various manufacturers.In the course of the study, the drives of the HGST, Hitachi, Samsung, ST, Toshiba, and WDC trademarks operated in the Backblaze largest commercial data centre were analysed. As a result of the analysis, the relationship between the specified parameter and such parameters as 3 spinup time (time of spinning the disk package from standstill to operating speed), 4 start/stop count (counting the spindle start/stop cycles), 12 power cycle count (number of fulldrive switching on/off cycles), 192 power-off retract count (the number of shutdown cycles, including emergencies), and 193 load cycle count (the number of magnetic head block moves in the parking zone/in working position cycles). It is shown that the nature of the change in the values of the considered parameters depends on the manufacturer of the hard drives. It is proposed to carry out an individual assessment of the information storage device rotation mechanism reliability using the parameters identified as a result of the study.